2018
DOI: 10.5812/aapm.74243
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Arterial and Central Venous Blood Gases Values in Patients Undergoing Mechanical Ventilation after Cardiac Surgery

Abstract: BackgroundThe most straightforward method of ascertaining arterial PO2, PCO2, and other components of blood gas is to measure them directly from a blood sample. In situations in which arterial puncture cannot be achieved or may be technically difficult, the venous blood sample can be used.MethodsIn a prospective analytical study, 80 patients undergoing mechanical ventilation after open-heart surgery in the intensive care unit were evaluated. Simultaneous, matched arterial and central venous blood gas samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Among studies on patients with any clinical contexts (metabolic, respiratory, or complex acid-base disorders), a considerable heterogenicity in the results was seen [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Bohloli [16] suggested using single regression prediction models to predict arterial PCO 2 and HCO 3 , to replace ABG with PVBG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among studies on patients with any clinical contexts (metabolic, respiratory, or complex acid-base disorders), a considerable heterogenicity in the results was seen [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Bohloli [16] suggested using single regression prediction models to predict arterial PCO 2 and HCO 3 , to replace ABG with PVBG.…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted on patients undergoing mechanical ventilation after open-heart surgery in the ICU revealed that central venous saturation O 2 did not consistently predict arterial saturation O 2 . Nonetheless, the study authors suggested substituting ABG analysis with CVBG analysis in specific situations [ 15 ]. Malinoski et al [ 14 ] compared ABG and CVBG values of pH, pCO 2 , and base excess but not those of HCO 3 and pO 2 in mechanically ventilated trauma patients admitted to ICU.…”
Section: Reviewmentioning
confidence: 99%